A05 Early transcriptional modifications of the developing brain in huntington disease. (12th September 2022) - Kacher, Radhia; Six, Julie; Coutelier, Marie; Hilab, Rania; Guegan, Justine; Durr, Alexandra; Humbert, Sandrine
Abstract : Huntington disease (HD) is an inherited neurological disease caused by a pathological CAG repeat expansion in the HTT gene encoding an abnormal glutamine repeat in the huntingtin protein (HTT). Given the adult-onset of this disease, the neurological symptoms, and the neuronal cell death, many studies focused on describing the effects of the mutant protein in adult neurons. However, HTT is expressed very early and plays a fundamental role in brain development. Specifically, HTT is required for mitotic spindle orientation, for maintaining the pool of cortical progenitors and at later stages for multipolar-bipolar transition and migration of newborn neurons in the mouse cortex. Mutant HTT impairs these mechanisms, resulting in thinner cortex in HD mice. In presymptomatic mouse models and patients, brain MRI studies have revealed cortical and striatal abnormalities decades before overt clinical signs. These defects could arise from an abnormal brain development in HD. For these reasons, we initiated a program to explore human brain development in HD and found that mutant HTT reduces the number of proliferating cells and triggers more neural progenitors to prematurely enter lineage specification. Yet, a lot remains unknown on the underlying molecular mechanisms. Here, we performed an RNAseq analysis on the developing cortex of fetuses carrying an HD-causing mutation compared to control fetuses at the same age. We show that mutant HTT impairs transcriptional regulations of human neurodevelopment and postulate that this may affect disease progression or onset. To go further, we are also exploring transcriptomic alteration using single nuclei RNAseq.